Using genomics to examine the persistence of Streptococcus pneumoniae serotype 19A in Ireland and the emergence of a sub-clade associated with vaccine failures. Issue 35 (16th August 2021) - Corcoran, M.; Mereckiene, J.; Cotter, S.; Murchan, S.; Lo, S.W.; McGee, L.; Breiman, RF.; Cunney, R.; Humphreys, H.; Bentley, S.D.; Gladstone, R.A.
Highlights: Despite PCV13 introduction serotype 19A is responsible for ~ 10% of IPD in Ireland. Sequencing revealed a diverse collection of clonal groups circulating within 19A. Vaccine failure/breakthrough cases were more frequently associated with GPSC1-CC320 than other GPSCs (p = 0.0001). A unique Irish sub-clade (n = 25) contained five of the ten 19A vaccine failure breakthrough cases. All sub-clade isolates contained a galE gene rarely observed elsewhere (n = 37/13454). The galE gene may contribute to the persistence of serotype 19A in this population. Abstract: Background: Streptococcus pneumoniae serotype 19A remains a significant cause of invasive pneumococcal disease (IPD) in Ireland despite the successful introduction of a 13-valent pneumococcal conjugate vaccine (PCV13) in 2010 which reduced the overall incidence of IPD in children. Methods: Invasive Streptococcus pneumoniae serotype 19A isolates from the Irish reference laboratory between 2007–08 and 2017–18 were analysed using whole genome sequencing (WGS) to investigate the persistence of this vaccine-preventable serotype. We compared the entire national 19A collection to other international collections using a standardised nomenclature of Global Pneumococcal Sequencing Clusters (GPSC). Results: Expansion of GPSCs and clonal complexes (CCs) may have been associated with vaccine introduction and antimicrobial prescribing policies. A sub-clade of GPSC1-CC320 (n = 25) unique to Ireland, included five of the ten vaccine failures/breakthrough cases identified (p = 0.0086). This sub-clade was not observed in a global GPSC1-CC320 collection. All isolates within the sub-clade (n = 25) contained a galE gene variant rarely observed in a global pneumococcal collection (n = 37/13454, p < 0.001) nor within GPSC1-CC320 (n = 19/227) (p < 0.001). The sub-clade was estimated to have emerged at the start of the PCV-vaccine era (ancestral origin 2000, range 1995–2004) and expanded in Ireland, with most isolated after PCV13 introduction (n = 24/25). Conclusions: The identification of a sub-clade/variant of serotype 19A highlights the benefit of using WGS to analyse genotypes associated with persistence of a preventable serotype of S. pneumoniae . Particularly as this sub-clade identified was more likely to be associated with IPD in vaccinated children than other 19A genotypes. It is possible that changes to the galE gene, which is involved in capsule production but outside of the capsular polysaccharide biosynthesis locus, may affect bacterial persistence within the population. Discrete changes associated with vaccine-serotype persistence should be further investigated and may inform vaccine strategies.